Black pigment formulation in dye application / Amin Faisal Ahmad Sanusi - Ahmad Sanusi, Amin Faisal (2017)
Black pigment is already been produced in many kind of industry. For the production of black pigment is mainly from the carbon black that black is composed of fine particles consisting mainly of carbon. Various features of carbon black are controlled in production by partially combusting oil or gases. In order to get the glossy look in the dye application, stainless steel flake will be chosen due to its less reactivity compared to other metallic or glossy pigment.